Gender Confirmation Surgery: Moving Forward. Issue 5 (July 2019) - Schechter, Loren S.; Cohen, Mimis
Abstract : Abstract: Facial surgery can help facilitate an individual's social transition and alleviate gender dysphoria. As such, surgical requests for feminizing and masculinizing procedures continue to increase. Surgical management requires knowledge of anatomy and anatomic differences as well as an understanding of social challenges faced by transgender and gender diverse individuals. Here, the authors provide a brief overview of gender confirmation surgery specific to the head and neck and craniofacial skeleton. In addition, the authors explore barriers to accessing healthcare for transgender and gender diverse individuals throughout the world.